The impact of entrepreneurship on economic growth: Empirical evidence in the Mekong Delta - Ho, Duc Hung; Pham, Minh Tien; Tran, Van Huu (Journal of Finance - Marketing Research, 2023)
Entrepreneurship is the main motivation for economic development, and a large amount of literature analyzing the impact of entrepreneurship on solid growth and sustainable relationships has appeared. This paper aims to quantify the impact of entrepreneurship on economic growth using balanced panel data from 8 provinces in the Mekong Delta region over 20 years. Two indicators of entrepreneurship (Private Employment Rate, Self-Employment Rate) are identified and incorporated into the traditional growth regression model demonstrated using the Feasible Generalized Least Square (FGLS) method. The results show that entrepreneurship has a positive impact on economic growth and this finding is very strong through the private employment rate of 8 Mekong Delta provinces but does not provide enough evidence that the self-employment rate has a positive impact on growth. Public policies that promote entrepreneurship should be expected to positively influence economic growth.